Optimal power flow algorithms for large-scale distribution networks to mitigate voltage unbalance and power losses with energy resources - Ayikpa, Malinwo Estone [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
The integration of solar photovoltaic generation in the distribution system has been largely carried out in small- or medium-scale networks without in-depth analysis. The interaction of PV systems with conventional voltage regulation equipment can cause negative impacts to the grid that need to be studied, especially when PV inverters provide reactive power control to the grid. Moreover, the planning and operation of distribution networks with the integration of distributed generations and capacitor banks was usually done on small-scale and medium-scale systems. The network topology presents a radiality problem with some metaheuristic algorithms that deal with feeder reconfiguration in large-scale distribution systems. Based on the problems mentioned above, this work presents an AC three-phase optimal power flow (TOPF) that minimizes voltage unbalance in large-scale distribution networks, with optimal adjustment of voltage regulator taps and the integration of PV plants operating at maximum power with reactive power control of inverters. The simulations were performed using the IEEE 123 node feeder with three-phase and single-phase PV plants, respectively, and results presented a better understanding of the impacts of distributed PV systems on large-scale distribution networks in terms of power quality. The TOPF developed in this work is based on the current injection method and the optimal solution was achieved using the primal-dual interior point method. Later in this work, we address an optimal power flow based on distribution feeder reconfiguration (DFR), with the integration of distributed generation (DG) and capacitor bank (CB) into large-scale distribution networks to minimize power losses. The stochastic fractal search algorithm (SFS) has been used to solve this problem. The proposed algorithm was tested on the 33-bus, 69-bus, 119-bus, and 136-bus distribution networks. Different simulation cases have been carried out, and the results showed a significant impact on reducing the losses and enhancing the minimum voltage value of the feeder, especially when DGs and CBs are simultaneously addressed in the DFR problem.

A integração da geração solar fotovoltaica no sistema de distribuição tem sido realizada principalmente em redes de pequena ou média escala, sem uma análise aprofundada. A interação de sistemas fotovoltaicos com equipamentos convencionais de regulação de tensão pode causar impactos negativos na rede elétrica, os quais precisam ser estudados, especialmente quando os inversores fotovoltaicos fornecem controle de potência reativa à rede. Além disso, o planejamento e a operação de redes de distribuição com a integração de geração distribuída e bancos de capacitores geralmente são realizados em sistemas de pequena e média escala. A topologia da rede apresenta um problema de radialidade com alguns algoritmos meta-heurísticos que lidam com a reconfiguração de alimentadores em sistemas de distribuição de grande escala. Este trabalho apresenta um fluxo de potência ótimo trifásico CA (FPOT) que minimiza o desequilíbrio de tensão em redes de distribuição de grande escala, com ajuste ótimo dos taps do regulador de tensão e a integração de usinas fotovoltaicas operando em potência máxima com o controle de potência reativa dos inversores. As simulações foram realizadas usando o alimentador de nós IEEE 123 com usinas fotovoltaicas trifásicas e monofásicas, respectivamente, e os resultados apresentaram uma melhor compreensão dos impactos dos sistemas fotovoltaicos distribuídos em redes de distribuição de grande escala em termos de qualidade de energia. O FPOT desenvolvido neste trabalho é baseado no método de injeção de corrente e a solução ótima foi alcançada usando o método primal-dual de ponto interior. Posteriormente neste trabalho, abordamos um fluxo de potência ótimo baseado na reconfiguração do alimentador de distribuição (RAD), com a integração de geração distribuída (GD) e banco de capacitores (BC) em redes de distribuição de grande escala para minimizar as perdas de energia. O algoritmo de busca fractal estocástico (BFE) foi utilizado para resolver este problema e testado nos sistemas de 33, 69, 119 e 136 barras e os resultados mostraram um impacto significativo na redução das perdas com a integração simultânea de GDs e CBs nos sistemas.
Algoritmos de fluxo de potência ótimo para redes de distribuição de grande escala para mitigar o desequilíbrio de tensão e as perdas de potência com recursos energéticos
Keywords: Electric power systems; Nonlinear programming; Combinatorial optimization; Electric power distribution; Photovoltaic power plants; Three-phase optimal power flow; Primal-dual interior point method; Voltage unbalance; Distribution feeder reconfiguration; Stochastic fractal search; Fluxo de potência ótimo trifásico; Método primal-dual de ponto interior; Usina fotovoltaica; Desequilíbrio de tensão; Reconfiguração de rede de distribuição; Busca fractal estocástica